Preoperative Serum CA125 and Plasma Fibrinogen Levels as Predictors of Lymphovascular Space Invasion in Endometrial Cancer - Zahraa Dhirar Yousif; Hayder B. Al-Shammaa (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Lymphovascular space invasion has been shown to be a predictor of lymph node metastasisand decreased survival in patients with endometrial cancer. Unfortunately, LVSI status is most commonlynot available until after hysterectomy at the time of preparation of the final Pathology report. Therefore;LVSI status represent additional information to be considered in decision making process regarding whetherto perform lymphadenectomy or to deliver adjuvant therapy. Thus, it was important to find biomarkers topredict the risk of LVSI before surgery.Objective: To evaluate the value of serum CA125 and plasma fibrinogen for prediction of lymphovascularspace invasion in women with endometrial cancer.Study Design: A prospective observational cross-sectional study.Settings: was carried out in the Department of Obstetrics and Gynecology/ Baghdad Teaching Hospital, andNursing Home Hospital in Medical City complex, Baghdad, Iraq, over a period of 1 year starting from thefirst of December 2017 to the end of November 2018.Patients and Methods: Fifty-five women with endometrial cancer undergoing surgery were included inthis study. We compared the preoperative level of serum CA125 and plasma fibrinogen with postoperativehistopathological report regarding LVSI, the results were statistically analyzed.Results: (16.4%) of the patients with positive lympho-vascular invasion. CA-125, Fibrinogen, were highlysignificantly increased in patients with positive LVSI. Sensitivity was (88.9%), specificity (95.7%), negativepredictive value (95.0%), positive predictive value (91.0%),and accuracy of the test was (92.3%)whenthe cutoff value for CA125 was (28.75U/ml) while for plasma fibrinogen in cutoff value (317mg/dl)thesensitivity was (100.0%), specificity (95.7%),negative predictive value (100.0%), positive predictive value(95.9%) and the accuracy of the test was (97.8%)Conclusion: The preoperative assessment of serum CA 125 and plasma fibrinogen could be used to predictthe LVSI in endometrial cancer.